Dementia with Lewy bodies - a disease from the border of Neurology and Psychiatry - case report - Kroc, Lukasz; Szczepkowska, Aleksandra (Journal of Education, Health and Sport, 2017)
This article presents the case of 88 years old patient diagnosed and treated for dementia with Lewy bodies.